2004
DOI: 10.1002/srin.200405812
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Steel Thixoforming Tool Materials by High Temperature Compression Tests

Abstract: The experimental set-up and the results of high temperature compression tests for the characterization of tool materials for steel thixoforming are presented. The scope of this test is to reproduce the load profile of steel thixoforming processes consisting of mechanical, thermal, tribological, and chemical components on the forming mould. Tool materials were chosen following a concept within the Collaborative Research Center -SFB 289 -"Forming of metals in the semi-solid state and their properties". Three mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…It was found around 1437 • C when using the "cold" die and the 40 mm/s ram speed. Kopp et al (2004) and Li et al (2005) presented the same kind of results obtained for other steel grades. Carrying out compression tests on aluminium alloys, Kang et al (1999) also found similar results.…”
Section: Shape Of Extruded Partssupporting
confidence: 80%
“…It was found around 1437 • C when using the "cold" die and the 40 mm/s ram speed. Kopp et al (2004) and Li et al (2005) presented the same kind of results obtained for other steel grades. Carrying out compression tests on aluminium alloys, Kang et al (1999) also found similar results.…”
Section: Shape Of Extruded Partssupporting
confidence: 80%
“…In the SFB289 project [56], three types of materials have been compared: thin film PVD and PACVD; thermally sprayed thick coatings and bulk ceramic materials. The results showed that the behaviour was sensitive to the stresses at the surface of the die and therefore the die should be made of different materials in different positions.…”
Section: Tools and Forming Diesmentioning
confidence: 99%
“…The performance of PVD oxide coatings, nevertheless, deserves attention. TiAlN/␥-Al 2 O 3 and TiAlN/t-ZrO 2 PVD coated plates had not shown any visible signs of coating failure or rupture at the surface [23,51,52].…”
Section: Resultsmentioning
confidence: 99%